Carbon fibre lattice strain mapping via microfocus synchrotron X-ray diffraction of a reinforced composite. (5th November 2022) - Srisuriyachot, Jiraphant; McNair, Sophie A.M.; Chen, Yang; Barthelay, Thomas; Gray, Rob; Bénézech, Jean; Dolbnya, Igor P.; Butler, Richard; Lunt, Alexander J.G.
Abstract: Synchrotron X-ray diffraction (SXRD) strain analysis is well established for high crystalline materials such as metals and ceramics, however, previously it has not been used in Carbon Fibre Reinforced Polymer (CFRP) composites due to their complex turbostratic atomic structure. This paper will present the feasibility of using SXRD for fibre orientation and lattice strain mapping inside CFRPs. In particular, it is the first time that the radial 002 and axial 100 strains of carbon fibre crystal planes have been analysed and cross-validated via numerical multi-scale simulation in a two-scale manner. In order to simplify the analysis and provide comparable estimates, an UniDirectional (UD) CFRP formed into a well-established humpback bridge shape was used. The lattice strain estimates obtained from SXRD showed localised stress concentrations and effectively matched the numerical results obtained by modelling. The mean absolute percentage differences between the two were 25.8% and 28.5% in the radial and axial directions, respectively. Differences between the two measurements are believed to originate from the non-uniform thermal history, forming geometry and tool-part interaction which leads to localised residual strains in the laminate which are unable to be fully captured by the numerical simulation performed. The carbon fibre microstructures of the inner plies adjacent to the tool were found to be significantly influenced by these factors and therefore the largest errors were observed at these locations. The approach presented has significant promise and implications for research into the micromechanics of composite materials and areas for future improvement have been outlined. Graphical abstract: Image 1 Highlights: First quantification of micro-scale lattice strain in Carbon Fibre Reinforced Polymers (CFRPs). Microfocus Synchrotron X-ray diffraction used to quantify microstructural changes. Effective match between experimental lattice strain and simulations. Errors/uncertainties and improvements identified to overcome challenges associated with the turbostratic structure of CFRPs.